FRI0125 INDIVIDUAL PATIENT DATA META-ANALYSIS OF THE EFFECTIVENESS OF TOCILIZUMAB ON INHIBITING RADIOGRAPHIC PROGRESSION IN RHEUMATOID ARTHRITIS. (June 2019) - Verhoeven, Maxime; Tekstra, Janneke; Jacobs, Johannes W. G.; Jacob, M; Laar, van; Bijlsma, Johannes Wj; Pethoe-Schramm, Attila; Borm, Michelle; Lafeber, Floris; Welsing, Paco
Abstract : Background: Several studies have shown that treatment with tocilizumab (TCZ) may reduce radiograph progression compared to treatment with methotrexate (MTX) in rheumatoid arthritis (RA). However, individual studies were not powered to detect differences in the incidence of progression. By combining several studies, a more precise estimate can be obtained. Furthermore, by using individual patient data (IPD), outcome definitions and methods can be harmonized for a valid combined analysis. Objectives: To determine the effectiveness of treatment with TCZ on radiographic progression compared to MTX in RA patients over two years. Methods: Randomized controlled trials in RA patients using TCZ as one of the treatment arms with radiographic damage assessed on radiographs at baseline and after two years were identified and IPD obtained. The primary endpoint was defined as any radiographic progression over two years. Secondary endpoint was the amount of joint damage progression (points per time unit, expressed as incidence rate). Analyses were performed on total scores and for erosions and joint space narrowing (JSN) separately. TCZ strategies were compared with the control strategies. Within the TCZ strategies, a comparison between monotherapy and the combination with MTX was made. A two-step IPD meta-analysis was performed. In the first step, data of the individual trials were analysed using logistic regression and zero-inflated Poisson models. In the second step association measures (odds ratio's (OR) and incidence rate ratio's (IRR)) of individual trials were pooled using random effect models in Review Manager 1 . A subgroup analysis was performed on early versus established RA. All analyses were adjusted for baseline DAS28 and Sharp van der Heijde (SvdH) score to provide a more precise treatment effect estimate. Results: Five trials were identified, one trial 2 using a tight-control treat-to-target approach, and the four other RCTs 3-6 allowed the control group to start TCZ after 6 months or 1 year when the treatment target was not reached. Two trials were performed in early RA 1–2 . The dose of TCZ was tapered down in two studies 2, 6 . IPD of 4 trials could be obtained and were included (n=2439 randomized to TCZ arm and n=791 to control arm, MTX in all cases) 2–5 . The radiographs, performed at baseline and after two years, were all assessed with the SvdH method. Due to missing radiographic data, 1766 patients were evaluated in the TCZ arms and 543 patients in MTX arms. Patient characteristics are shown in Table 1 . The occurrence of any radiographic progression was statically significantly less in the TCZ arms compared to MTX arms (pooled OR 0.76 [95%CI 0.67 to 0.86]). The effect for erosions (OR 0.77 [95%CI 0.67 to 0.88]) was stronger than for JSN (OR 0.88 [95%CI 0.78 to 0.98]) with both being in favour of TCZ. No clear differences between early and established RA were observed for any progression. Any radiographic progression did not occur statistically significantly more often in the TCZ monotherapy group compared to the combination group. No statistically significant difference were observed for the amount of radiographic progression. Conclusion: Based on this individual patient data meta-analysis, radiographic progression was less common in TCZ-treated patients compared to MTX-treated patients in RCTs, possibly more for progression of erosions. No difference was observed between TCZ used as monotherapy or in combination with MTX. Reference: [1] Review Manager (RevMan) [Computer program]. Version 5.3. Copenhagen: The Nordic Cochrane Centre, The Cochrane Collaboration, 2014. Disclosure of Interests: Maxime Verhoeven: None declared, Janneke Tekstra: None declared, Johannes W. G. Jacobs Grant/research support from: Roche, Consultant for: Roche, Jacob M. van Laar Grant/research support from: Genentech, Consultant for: F. Hoffmann-La Roche, Johannes WJ Bijlsma Grant/research support from: The department of the author who included patients (JWJB) in the U-Act-Early trial received reimbursements from Roche Nederland BV. JWJB reported grants and fees from Roche, AbbVie, Bristol-Myers Squibb, Merck Sharp & Dohme, Pfizer, and UCB University Medical Center Utrecht, Utrecht University, Consultant for: SUN Pharma, Speakers bureau: Lilly, Roche, Attila Pethoe-Schramm Shareholder of: F. Hoffmann-La Roche, Employee of: F. Hoffmann-La Roche, Michelle Borm Employee of: An employee of Roche Nederland BV, Floris Lafeber Shareholder of: ArthroSave, Grant/research support from: FOREUM; Dutch Arthritis Society, Paco Welsing: None declared